(untitled) (Physical Culture and Sport: Scientific Perspective, 2025)
The article provides an overview of studies conducted between 2019 and 2024 on the impact of adaptive sports on the quality of life of individuals after lower limb amputation. A comprehensive analysis of the main structural and content-related advantages and gaps in scientific research on the resocialization of individuals after lower limb amputation is carried out. Key aspects that complicate social reintegration and negatively affect the quality of life of people after lower limb amputation are revealed. Thematic dimensions of quality of life and resocialization of individuals after lower limb amputation are identified, which require further scientific study in the future. The study analyzes 23 scientific publications published in accredited medical journals of categories “A” and “B.” The following methods and approaches were used in the analysis of scientific research: systematic, critical-analytical, descriptive, and historiographical. The scientific study reveals that individuals after lower limb amputation most often experience depressive and anxiety disorders. This is due to the following factors or components: visual adaptation to a new physicality; grief over pain and loss of a limb; inability to fully satisfy one’s own needs; feelings of insecurity. It has been determined that the central challenges in the social dimension for people after lower limb amputation are as follows: insufficient adaptation of the environment to human needs; weather and climate restrictions; insufficient financial security. It has been found that the key component of a person’s comprehensive recovery is their involvement in adaptive sports (wheelchair basketball, para-golf, boccia). It has been found that various types of adaptive sports contribute to improving a person’s physical condition and help develop social communication skills. It has been determined that a person’s integration into any adaptive sport contributes to a reduction in the manifestation of mental and psychological problems, in particular anxiety or depression. It has been demonstrated that the competitive sports process effectively influences the construction of a person’s social identity after lower limb amputation.